Comparison of the bactericidal efficacy of photodynamic therapy, 2.5% sodium hypochlorite, and 2% chlorhexidine against Enterococcous faecalis in root canals; an in vitro study - Shahram Vaziri; Ali Kangarlou; Razieh Shahbazi; Amin Nazari Nasab; Mandana Naseri (Dental Research Journal, 2012)
Background : Enterococcus faecalis has been widely used as a valuable microbiological pathogen for in vitro studies due to its ability to successfully colonize the root canal in a biofilm-like style, invade dentinal tubules, and resist endodontic treatment procedures.The aim of this study was to compare the bactericidal efficacy of photodynamic therapy (PDT), 2% chlorhexidine, 2.5% NaOCl, and combination of PDT and 2.5% NaOCl against E. faecalis. Materials and Methods: Sixty single-rooted teeth had their canals contaminated with E. faecalis in brain heart infusion broth and were incubated for 48 hours.The canals were then subjected to 2% chlorhexidine, 2.5% NaOCl, PDT (red light emitting diode 625 nm+ Toludine Blue) and PDT + 2.5% NaOCl. Controls consisted of no treatment (positive control) and without inoculation of bacterium (negative control). Following treatment, the canal contents were sampled with sterile paper points.The samples were dispersed in transport medium, serially diluted, and cultured on blood agar to determine the number of colony forming units (CFU). Data were analyzed by Mann-Whitney U test at 5% significance level. The significance level for all analyses was set at P <.05. Results: Combination of PDT and 2.5% NaOCl achieved maximum reduction in recovered viable bacteria, no viable bacteria was observed after treatment of PDT + 2.5% NaOCl. Conclusion: Combination of PDT and 2.5% NaOCl simultaneously is effective in the elimination of E. faecalis from dentinal tubules under the conditions of this study.